Comparison of Endometrial Tissue Co-cultures in Fertile and Infertile Women with Implantation Failure - Bahar, Leyla; Kahraman, Semra; Baykal, Tülin; Reşitoğlu, Bora (Fırat University, 2012)
Objective: Failure of implantation is one of the most important factors affecting the success of in vitro fertilization (IVF) applications. In this study, women in fertile and infertile women with previous implantation failure in IVF applications are aimed to be compared within their endometrial cocultures. Materials and Methods: Ten fertile women and the seventeen women with recurrent implantation failure (RIF) were included to the study, endometrium biopsy samples were taken. Monolayer of co-culture technique was applied to the endometrial samples. In the endometrial co-culture of fertile and RIF group individuals, glands and stromal cells were evaluated by invert microscope and statistical analysis was performed. Results: Co-cultures of the endometrium of fertile and RIF group women were compared with the microscope. Morphological differences were observed for the development of gland and stromal cells. In the fertile group, development of endometrial co-culture cells was better than RIF group. RIF group co-culture cells, less developed and had less number. Development of RIF group cells was less than quantitative terms. As a result of comparison of gland and stromal cells statistically, in fertile and RIF group, significant difference was observed. Conclusion: When the endometrial co-cultures of fertile and RIF women were compared, the difference was found significant not only morphologically but also statistically. However, it was stated that the endometrial co-culture applications increase the implantation rates in RIF patients. So new studies are needed to explain the disclosure of molecular mechanisms of implantation and to improve the quality of the embryo development.

Amaç: İmplantasyon başarısızlığı, in vitro fertilizasyon (IVF) uygulamalarında başarıyı etkileyen en önemli faktörlerden biridir. Bu çalışmada, fertil kadınların ve daha önceki IVF uygulamalarında implantasyon başarısızlığı olan infertil kadınların, endometrial ko-kültürlerinin karşılaştırılması amaçlanmıştır. Gereç ve Yöntem: Çalışmaya fertil on kadın ve Tekrarlayan İmplantasyon Başarısızlığı (TİB) olan onyedi kadın dahil edildi, endometriyumlarından biyopsi örnekleri alındı. Endometrial örneklere monolayer ko-kültür tekniği uygulandı. Fertil ve TİB grubu bireylerin endometrial ko-kültüründe gland ve stromal hücreler invert mikroskopla değerlendirildi ve istatiksel analizi yapıldı. Bulgular: Fertil ve TİB grubu kadınların endometrial ko-kültürleri mikroskobik olarak karşılaştırıldı. Gland ve stromal hücrelerin gelişimi açısından morfolojik farklar gözlendi. Fertil grupta endometrial ko-kültür hücrelerinin gelişimi TİB grubundan daha iyiydi. TİB grubu hücreler, daha az gelişmişti ve daha az sayıya sahipti. Kantitatif açıdan TİB grubu hücrelerinin gelişimi daha azdı. Fertil ve TİB grubunda gland ve stromal hücrelerin karşılaştırılması sonucunda istatistiksel açıdan anlamlı farklılık tesbit edildi. Sonuç: Fertil ve TİB olan kadınların endometrial ko-kültürleri karşılaştırıldığında sadece morfolojik olarak değil ayrıca istatistiksel açıdan da anlamlı fark tesbit edilmiştir. Ancak, endometrial ko-kültür uygulamalarının, TİB hastalarında implantasyon oranlarını arttırdığı belirtilmektedir. O halde, implantasyonu ve embriyo gelişim kalitesini artıran moleküler mekanizmaların açıklanmasını sağlayacak yeni çalışmalara ihtiyaç vardır.
Fertil ve İmplantasyon Başarısızlığı Olan İnfertil Kadınlarda Endometrial Doku Ko-kültürlerinin Karşılaştırılması